The Relationship Of The Climate Change Factor With The Event Of Dengue Hemorrhagic Fever In Palu City 2013-2017 - Muhammad Jusman Rau; Siti komaria; Pitriani Pitriani (Tadulako University, 2019)
Temperature, rainfall and relative humidity are considered important climatic factors that contribute to the growth and spread of mosquito vectors and potential dengue outbreaks. The purpose of this study was to determine the relationship of air temperature, humidity, and rainfall with the incidence of DHF in the city of Palu in 2013-2017. This type of research is quantitative with correlation design. The sampling technique uses total sampling. The data source uses secondary data, namely the number of DHF events from the Palu City Health Office and climate data from the Mutiara Palu Meteorological Station. Data analysis using Pearson correlation test, the results of the study showed the strength of the temperature relationship with the incidence of DHF was very weak (r = -0.087), negative patterned and there was no significant relationship (ρ = 0.253). The strength of the humidity relationship with the incidence of DHF was very weak (r = 0.029), positive patterned and there was no significant relationship (ρ = 0.412). The relationship strength of rainfall with the incidence of DHF was very weak (r = 0.001), positive patterned and there was no significant relationship (ρ = 0.496). The conclusion was not found a meaningful relationship between the variables of temperature, humidity, and rainfall with the incidence of DHF. To overcome the DHF incident, it is expected that the Palu City Health Office can increase efforts to control DHF by increasing environmental improvement by running programs such as 3M Plus, Mosquito Nest Eradication (PSN), Abatization, and fogging.